(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In the expression ‘population geography’, the term ‘population’ signifies the subject matter and ‘geography’ refers to the perspective of investigation. Population geography implies the investigation into human covering of the earth and its various facets with reference to physical and cultural environment. Although population geography is, in the early 21st century, a well-established subfield of human geography, this was not always the case.